Toward a quantified assessment of total body surface area from anthropometric measurements for patients with burn injuries. (2017) - Desbois, Adrien; Perreault, Isabelle; Chartrand, Gabriel; Cresson, Thierry; Gervais, Sylvie; Guise, Jacques A. De
The amount of replacement fluid a burn patient requires to survive depends on the ratio (RBSA) of burned body surface area to the total body surface area (TBSA). The 2D methods used by clinicians are imprecise. In this paper, preliminary result of a proposed approach using anthropometric measurements and MakeHuman (MH) software to evaluate RBSA is presented. To assess RBSA accurately with a personalised 3D model of the burn patient, a first critical step is to find a limited set of measures for TBSA assessment. 20 anthropometric measurements were acquired virtually on 40 3D models generated with MH software. Using several multiple regression analyses, it was demonstrated that four to seven measures are sufficient to obtain an accurate TBSA. These preliminary results highlight the relevance of using software such as MH, to assess TBSA of patients with major burn injuries based on a limited set of measures.